2021
DOI: 10.1139/apnm-2020-0349
|View full text |Cite
|
Sign up to set email alerts
|

A history of smoking does not reduce long-term benefits of cardiac rehabilitation on cardiorespiratory fitness in men and women with cardiovascular disease

Abstract: Smoking is an important risk factor for cardiovascular disease and all-cause mortality. Cardiac rehabilitation (CR) is effective for reducing the risk of recurrent cardiac events through improving cardiorespiratory fitness (CRF). Little is known about the influence of smoking on CRF throughout long-term CR. The purpose of this analysis was to compare CRF trajectories among individuals with positive and negative smoking history enrolled in long-term CR. Participants had a positive smoking history if they curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…However, FRS, which incorporates smoking status, was significantly associated with EC in patients and controls. In the literature, there are conflicting results regarding the impact of smoking history on EC where several studies found no impact of smoking on EC changes 36 . These results with ours suggest smoking does not directly affect EC but may have an overall effect with the other traditional risk factors on decreased EC in AxSpA.…”
Section: Discussionsupporting
confidence: 43%
“…However, FRS, which incorporates smoking status, was significantly associated with EC in patients and controls. In the literature, there are conflicting results regarding the impact of smoking history on EC where several studies found no impact of smoking on EC changes 36 . These results with ours suggest smoking does not directly affect EC but may have an overall effect with the other traditional risk factors on decreased EC in AxSpA.…”
Section: Discussionsupporting
confidence: 43%
“…Quitting smoking, or reducing tobacco consumption, has been shown to be beneficial to health, as well as to reduce the risk of lung cancer and the likelihood of cardiovascular disease in cases of strong reductions in consumption, although it may not be a sufficient condition to reduce all-cause mortality [ 7 ]. In addition, smokers and ex-smokers have been found to have decreased cardiorespiratory [ 8 , 9 ], pulmonary [ 10 ], and functional [ 11 , 12 ] capacities. A reduction in global and mental self-perceived health (SPH) was also shown, being one of the reasons for smoking cessation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%